2014
DOI: 10.1103/physrevd.89.014002
|View full text |Cite
|
Sign up to set email alerts
|

Gluon bremsstrahlung by heavy quarks: Its effects on transport coefficients and equilibrium distribution

Abstract: The effects of gluon radiation by charm quarks on the transport coefficients e.g. drag, longitudinal and transverse diffusion and shear viscosity have been studied within the ambit of perturbative quantum chromodynamics (pQCD) and kinetic theory. We found that while the soft gluon radiation has substantial effects on the transport coefficients of the charm quarks in the quark gluon plasma its effects on the equilibrium distribution function is insignificant.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1
1

Relationship

4
3

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 26 publications
(22 reference statements)
2
25
0
Order By: Relevance
“…From a very straight forward relationq = 4B ⊥ (Mazumder et al, 2014), where B ⊥ is the transverse diffusion coefficient, we can arrive at the following plot where it has been observed that if we perform the calculation including the radiation off the heavy quark instead of taking only the elastic interactions, we can achieve a result for η/s which is closer to the band in Fig. 4 as predicted by experiments.…”
Section: Surasree Mazumder Et Alsupporting
confidence: 57%
“…From a very straight forward relationq = 4B ⊥ (Mazumder et al, 2014), where B ⊥ is the transverse diffusion coefficient, we can arrive at the following plot where it has been observed that if we perform the calculation including the radiation off the heavy quark instead of taking only the elastic interactions, we can achieve a result for η/s which is closer to the band in Fig. 4 as predicted by experiments.…”
Section: Surasree Mazumder Et Alsupporting
confidence: 57%
“…In the present work we find that the momentum diffusion of J/ψ is small i.e. the transfer of momentum between J/ψ and hadrons is inefficient which means that the shear viscosity is large [22]. This again indicates that the role of hadrons in the suppression of J/ψ in the high momentum domain is inconsequential compared to QGP.…”
Section: Summary and Discussionsupporting
confidence: 46%
“…The aim of the present work is to estimate the momentum diffusion coefficient of hot hadrons produced as a result of phase transitions from an expanding QGP formed in heavy ion collisions at relativistic energies. That is we would like to understand how efficiently the momentum of the J/ψ propagating through a hadronic medium is transferred to the medium enabling to estimate momentum diffusion or shear viscous coefficient of the medium [22]. Since J/ψ is used here as a probe to extract the coefficient of momentum diffusion for characterizing the medium, its detection in the final reaction channel is essential.…”
Section: Dynamicsmentioning
confidence: 99%
“…The transfer of momentum depends on the strength of the interaction and this can be used to assess the nature of the fluid -liquid or gas. Moreover, the shear viscosity of the system also signifies the ability to transfer momentum over a length scale ∼ mean free path, indicating that the coefficients of diffusion and shear viscosity are related quantities [86] (see ref. [87] for a review and references therein).…”
Section: Single Electron From the Heavy Flavoured Meson (Hfm) Decaymentioning
confidence: 99%